DOSE ASSESSMENT FOR ATMOSPHERIC DISCHARGE OF LONG-LIVED RADIONUCLIDES IN NUCLEAR POWER PLANT DECOMMISSIONING. Issue 2 (6th July 2020) - S, Chitra; Anand, S; Bhargava, Pradeep; Krishan, Jayant; Singh, Kapil Deo S; Kulkarni, M S; Sharma, D N
Abstract: Decommissioning of nuclear power plants is a multistage process involving complex operations like radiological characterization, decontamination and dismantling of plant equipment, demolition of structures, and processing and disposal of waste. Radioactive effluents released into the environment may result in exposure of population through various exposure pathways. The present study estimates the public dose due to atmospheric discharge of important radionuclides during proposed decommissioning activities of Indian Pressurized Heavy Water Reactors. This study shows that major dose contributing radionuclides are 60 Co followed by 94 Nb, 134 Cs, 154 Eu, 152 Eu, 133 Ba, 99 Tc, 93 Mo and 41 Ca. It is found that infant dose is higher than adult dose and major fraction of total dose ( 98%) is through ground shine and ingestion; other pathways such as inhalation and plume shine contribute only a small fraction. This study will be helpful in carrying out radiological impact assessment for decommissioning operations which is an important regulatory requirement.